MENINGKATKAN KETUNTASAN HASIL BELAJAR FISIKA SISWA DENGAN MODEL STAD (STUDENT TEAMACHIEVEMENT DIVISION) DISERTAI LKS - Budiarso, Aris Singgih (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2015)
This aim of study to describe m odel Student Team Achievement Division with worksheet to improvelearned yielding thoroughness student physicson X.4 physics class Balung Senior High School. The population of study is comprising X.4 class consist of 38 student, the purposive sampling use sampling area m ethod. The technique of data analysis beused descriptive data analysis. Based on the result of analysis gotten the learned yielding thoroughness student physicsuse m odel Student Team Achievement Division with worksheet on the matter dynamic power canincrease middle became increase.